Impact of Proton Pump Inhibitor Use on the Comparative Effectiveness and Safety of Prasugrel Versus Clopidogrel: Insights From the Treatment With Adenosine Diphosphate Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events After Acute Coronary Syndrome (TRANSLATE‐ACS) Study. Issue 10 (October 2016) - Jackson, Larry R.; Peterson, Eric D.; McCoy, Lisa A.; Ju, Christine; Zettler, Marjorie; Baker, Brian A.; Messenger, John C.; Faries, Douglas E.; Effron, Mark B.; Cohen, David J.; Wang, Tracy Y.
Abstract : Background: Proton pump inhibitors (PPIs) reduce gastrointestinal bleeding events but may alter clopidogrel metabolism. We sought to understand the comparative effectiveness and safety of prasugrel versus clopidogrel in the context of proton pump inhibitor (PPI) use. Methods and Results: Using data on 11 955 acute myocardial infarction (MI) patients treated with percutaneous coronary intervention at 233 hospitals and enrolled in the TRANSLATE‐ACS study, we compared whether discharge PPI use altered the association of 1‐year adjusted risks of major adverse cardiovascular events (MACE; death, MI, stroke, or unplanned revascularization) and Global Use of Strategies To Open Occluded Arteries (GUSTO) moderate/severe bleeding between prasugrel‐ and clopidogrel‐treated patients. Overall, 17% of prasugrel‐treated and 19% of clopidogrel‐treated patients received a PPI at hospital discharge. At 1 year, patients discharged on a PPI versus no PPI had higher risks of MACE (adjusted hazard ratio [HR] 1.38, 95% confidence interval [CI] 1.21‐1.58) and GUSTO moderate/severe bleeding (adjusted HR 1.55, 95% CI 1.15‐2.09). Risk of MACE was similar between prasugrel and clopidogrel regardless of PPI use (adjusted HR 0.88, 95% CI 0.62‐1.26 with PPI, adjusted HR 1.07, 95% CI 0.90‐1.28 without PPI, interaction P =0.31). Comparative bleeding risk associated with prasugrel versus clopidogrel use differed based on PPI use but did not reach statistical significance (adjusted HR 0.73, 95% CI 0.36‐1.48 with PPI, adjusted HR 1.34, 95% CI 0.79‐2.27 without PPI, interaction P =0.17). Conclusions: PPIs did not significantly affect the MACE and bleeding risk associated with prasugrel use, relative to clopidogrel. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01088503.